Bark water uptake promotes localized hydraulic recovery in coastal redwood crown. (9th November 2015) - Mason Earles, J.; Sperling, Or; Silva, Lucas C. R.; McElrone, Andrew J.; Brodersen, Craig R.; North, Malcolm P.; Zwieniecki, Maciej A.
Abstract: Coastal redwood ( Sequoia sempervirens ), the world's tallest tree species, rehydrates leaves via foliar water uptake during fog/rain events. Here we examine if bark also permits water uptake in redwood branches, exploring potential flow mechanisms and biological significance. Using isotopic labelling and microCT imaging, we observed that water entered the xylem via bark and reduced tracheid embolization. Moreover, prolonged bark wetting (16 h) partially restored xylem hydraulic conductivity in isolated branch segments and whole branches. Partial hydraulic recovery coincided with an increase in branch water potential from about −5.5 ± 0.4 to −4.2 ± 0.3 MPa, suggesting localized recovery and possibly hydraulic isolation. As bark water uptake rate correlated with xylem osmotic potential ( R 2  = 0.88), we suspect a symplastic role in transferring water from bark to xylem. Using historical weather data from typical redwood habitat, we estimated that bark and leaves are wet more than 1000 h per year on average, with over 30 events being sufficiently long (>24 h) to allow for bark‐assisted hydraulic recovery. The capacity to uptake biologically meaningful volumes of water via bark and leaves for localized hydraulic recovery throughout the crown during rain/fog events might be physiologically advantageous, allowing for relatively constant transpiration. Abstract : While coastal redwood intakes water via its leaves, bark's hydraulic role is not well understood. We find that hydraulic recovery of branches occurs only when the entire branch surface is wet (i.e. bark and leaves), suggesting that bark plays a critical role in above ground water uptake. Using historical weather data from typical redwood habitat, we demonstrate that a sufficient number of crown‐wetting hours occur annually to account for substantial hydraulic recovery. These findings raise novel ecological, evolutionary and biophysical questions about the hydraulics of bark.